The effect of heat pre-treatment on the anaerobic digestion of high-solid pig manure under high organic loading level - Li, Pengfei; Wang, Jianlin; Peng, Hao; Li, Qichen; Wang, Ming; Yan, Wencong; Boboua, Stopira Yannick Benz; Li, Wenzhe; Sun, Yong; Zheng, Guoxiang; Zhang, Hongqiong (Frontiers in Bioengineering and Biotechnology, 2022)
Since more and more large-scale farms appear in China and changes in fecal sewage source disposal, the production of high-concentration solid manure waste is also increasing, and its conversion and utilization are gaining attention. This study investigated the effect of heat pre-treatment (HPT) on the thermophilic anaerobic digestion (AD) of high-solid manure (HSM). Pig manure (PM) feed with a total solids of 13% was used for the HPT and subsequent anaerobic digestion (AD) test. The HPT was carried out at 60 °C, 80 °C, and 100 °C, respectively, for 15 minutes after the heating reached the set temperature. The results of HPT and batch AD test showed that the maximum soluble COD (SCOD) of 50.5 g·L-1 and methanation potential of 264.64 mL·g-1 VS were observed in the digestion of PM feed after pre-treatment at 100 °C, increasing by 24.57% and 28.76% compared to untreated manure, respectively. Another semi-continuous AD test explored the maximum volume biogas production rate (VBPR). It involves two organic loading rates (OLR) of 13.4 and 17.8 g VSadded·L-1·d-1. The continuous test exhibited that all the HPT groups could produce biogas normally when the OLR increased to the high level, while the digester fed with untreated PM showed failure. The maximum VBPR of 4.71 L·L-1·d-1 was observed from PM feed after pre-treated at 100 °C and running at the high OLR. This reveals that thermal treatment can weaken the impact of a larger volume of feed on the AD system. Energy balance analysis demonstrates that it is necessary to use a heat exchanger to reuse energy in the HPT process to reduce the amount of energy input. In this case, the energy input to energy output (Ei/Eo) ranged from 0.34 to 0.55, which was much less than one, suggesting that biogas increment due to heat treatment can reasonably cover the energy consumption of the pre-treatment itself. Thus combining HPT and high-load anaerobic digestion of PM was suitable.